Talent Management Implementation Strategy to Increase Retention in Managerial Positions: Case Study in Banjarbaru City - Rizqi Hidayah; Budi Kristanto (Dinasti International Journal of Education Management And Social Science, 2025)
Talent management plays an important role in improving managerial job retention, especially in the public sector. This study aims to explore talent management implementation strategies that can improve employee loyalty in Banjarbaru City. Using a descriptive qualitative approach, data were collected through in-depth interviews and document analysis. The results of the study indicate that competency development, performance-based rewards, and work-life balance policies are the main factors in reducing turnover. As well as providing practical recommendations for policy makers. This study also highlights the need for transparency in promotion and employee participation in policy making. The theoretical and practical implications of this study provide insights for more effective human resource management in the government sector. Further studies are recommended to expand the scope and use quantitative methods to increase the validity of the findings.